Advances and perspectives in the use of polymers in the environmental area: a specific case of PBS in bioremediation - Bedor,Priscilla Braga Antunes (2020)
Abstract Biodegradable polymers (e.g. poly(butylene succinate) - PBS) have been used in several sectors such as the environmental area, especially in bioremediation, in biological processes for conversion of pollutants into inorganic compounds. In this study, the foresight methodology for the use of biodegradable polymers, including PBS, reveals a publication rate of approximately 8.74 articles and 30.63 patents per year, between 2005 and 2019. However, the application of PBS, specifically, is still restricted to the environmental area, with only 3.0% of the 1484 works from this period. The results showed a more significant number of papers on the PBS application for synthesis, characterization, and application in the areas of Chemistry, Physics, and Pharmacy. In the area of bioremediation, only three studies related to PBS were found, revealing the lack of research and development to increase the contribution in the area of environmental recovery.